Вакцина против мафии: повесть / А.В. Мальцев - Мальцев А. В. (Русский бестселлер, 2001)
Экземпляры: ф.8 (20160413) / Инвентарный номер: 32259 / Цена: 18.00 / Авт.знак: М21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6